Kewenangan Dinas Pekerjaan Umum Dan Penataan Ruang Kota Bima Dalam Mewujudkan Penyelenggaraan Penataan Ruang - Aulia, Nur Rizki; Nurikah, Nurikah; Rayhan, Rayhan (Equality : Jurnal Hukum dan Keadilan, 2025)
Spatial Planning is a system of spatial planning, spatial utilization, and control of spatial utilization. Based on of Law Number 26 of 2007 concerning Spatial Planning, the Public Works and Spatial Planning (PWSP) of Bima City has the authority to realize the implementation of spatial planning. In its implementation, Bima City still has space utilization that is not in accordance with what has been determined by the government. As for the identification of the problem, how is the authority of the PWSP Office of Bima City in realizing the implementation of spatial planning based on Law Number 26 of 2007 concerning Spatial Planning? and how are the obstacles faced by the PUPR Office of Bima City in realizing the implementation of spatial planning based on Law Number 26 of 2007 concerning Spatial Planning? The theory used is the theory of authority and spatial planning theory. The method used is empirical juridical method with data analysis through a qualitative approach using primary data in the form of interviews with resource persons from the Spatial Planning Division of the PWSP Office of Bima City, and secondary data. The results of the research, the PWSP Office of Bima City exercises its authority in realizing the implementation of spatial planning in accordance with the provisions in Article 11 paragraph (1) and paragraph (2) of Law Number 26 of 2007 concerning Spatial Planning. The conclusion of this research is that the authority of the PWSP Office of Bima City is obtained by delegation and exercises its authority in the form of regulation, guidance, planning, utilization, and control of space. Its activities are in the form of issuing Regional Regulations and Mayor Regulations, as well as socialization to the community. They are also responsible for the preparation of spatial plans, coordination of spatial utilization, zoning, licensing, and supervision through monitoring and evaluation, and reporting. There are 4 obstacle factors, namely the inadequate competence of human resources organizing spatial planning, there are still laws and regulations related to space that need to be synchronized, limited budgets that do not support the implementation of spatial planning, and limited spatial planning information systems. The suggestion is that the PWSP Office of Bima City needs to improve socialization and spatial information systems.